Association between Vascular Bundles and Panicle Traits in F2 Population of Rice (Oryza sativa L.) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Bangladesh j. genet. biotechnol. 7 (1&2): 103-104, 2006 (June & December)